DIGITAL HUMAN RESOURCE MANAGEMENT IN PUBLIC SECTOR ORGANIZATIONS IN BORDER AREAS: A SYSTEMATIC REVIEW OF ADOPTION DRIVERS, BARRIERS, AND ORGANIZATIONAL OUTCOMES - Jurianto Gambir; Maria Cristiana Iman Kalis; M. Irfani Hendri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Digital transformation in the public sector has encouraged the use of Digital Human Resource Management (Digital HRM) as a strategic instrument for improving organizational efficiency and the quality of public services. Nevertheless, the available studies remain fragmented and have not yet provided a comprehensive synthesis of the relationships among adoption drivers, implementation barriers, and organizational outcomes, particularly in border areas that often face infrastructure and resource constraints. This study conducts a systematic literature review (SLR) to examine the role of Digital HRM in shaping organizational outcomes in the public sector and to identify the factors that influence its successful implementation. It also investigates the drivers and barriers affecting the adoption process. The review follows the PRISMA guidelines and uses Scopus as the primary database. Of the 320 articles identified at the initial stage, 60 remained after preliminary screening, and 30 empirical studies that met the inclusion criteria were analyzed in depth. The quality of each study was assessed using the Mixed Methods Appraisal Tool (MMAT), while the evidence was synthesized through thematic analysis. The findings show that Digital HRM adoption is influenced by technological, organizational, human, and institutional factors. Perceived usefulness, organizational readiness, and leadership support emerged as the most significant drivers, whereas resistance to change, inadequate infrastructure, and digital skills gaps were the most frequently reported barriers. Digital HRM was found to improve operational efficiency, service quality, employee performance, and the quality of decision-making. However, these relationships are often mediated by employee engagement and knowledge sharing. In border areas, limited connectivity and resources are particularly important in determining implementation effectiveness. This study contributes a more integrated synthesis of the relationships among drivers, barriers, and organizational outcomes in public-sector Digital HRM. By positioning border areas as the analytical context, it also broadens a theoretical perspective that has received limited attention. The findings are expected to support the development of Digital HRM policies and implementation strategies that are more responsive to field conditions and capable of adapting to existing constraints.